The French connection [videorecording (DVD)] - Friedkin, William; D'Antoni, Philip, 1929-2018; Hackman, Gene; Rey, Fernando, 1917-1994; Scheider, Roy; Moore, Robin, 1925-2008 (Twentieth Century Fox Home Entertainment, 2001)
Two New York City narcotics detectives learn of a scheme to smuggle a large quantity of heroin inside an automobile being shipped from France.